Relationship between Education Level and Performance of Medical Record Officers at the Mataram City Hospital: Hubungan Tingkat Pendidikan dengan Kinerja Petugas Rekam Medis di Rumah Sakit Umum Daerah Kota Mataram - Putra, Rizal Pratama Adi; Syamsuriansyah, Syamsuriansyah; Hasanah, Uswatun; S., Jihadil Qudsi; Halid, Musparlin (Procedia of Engineering and Life Science, 2024)
Efforts to improve the performance of health workers in hospitals are very important because of the various aspects related to efforts to improve health services. One of the vital units in the hospital is the medical record which with its duties is expected to support the quality of service by improving performance well. This study aims to determine the relationship between education level and the performance of medical record officers at the Mataram City Regional General Hospital. The research design used was quantitative analytic The research sample was 70 medical record officers with total sampling. The analysis in this study used univariate and bivariate analysis with a confidence level of 95% or a value of α < 0.05. This study shows that there is a relationship between educational background and performance with a p value = 0.000 < α value = 0.05. The level of education affects the performance of medical record officers at the Mataram City Hospital.